Biomimetic design of a dynamic M-O-V pyramid electron bridge for enhanced nitrogen electroreduction - Sun, Yuntong (2024)
Electrochemical nitrogen reduction reaction (eNRR) offers a sustainable route for ammonia synthesis; however, current electrocatalysts are limited in achieving optimal performance within narrow potential windows. Herein, inspired by the heliotropism of sunflowers, we present a biomimetic design of Ru-VOH electrocatalyst, featuring a dynamic Ru-O-V pyramid electron bridge for eNRR within a wide potential range. In situ spectroscopy and theoretical investigations unravel the fact that the electrons are donated from Ru to V at lower overpotentials and retrieved at higher overpotentials, maintaining a delicate balance between N2 activation and proton hydrogenation. Moreover, N2 adsorption and activation were found to be enhanced by the Ru-O-V moiety. The catalyst showcases an outstanding Faradaic efficiency of 51.48% at -0.2 V (vs RHE) with an NH3 yield rate exceeding 115 μg h-1 mg-1 across the range of -0.2 to -0.4 V (vs RHE), along with impressive durability of over 100 cycles. This dynamic M-O-V pyramid electron bridge is also applicable to other metals (M = Pt, Rh, and Pd).